Midterm outcomes of subcoronary stentless porcine valve versus stented aortic valve replacement. Issue 11 (13th August 2020) - Aranda‐Michel, Edgar; Bianco, Valentino; Dufendach, Keith; Kilic, Arman; Habertheuer, Andreas; Humar, Rishab; Navid, Forozan; Wang, Yisi; Sultan, Ibrahim
Abstract: Introduction: Stentless porcine xenografts are versatile bioprosthetic valves with the advantage of improved hemodynamics that mimic the function of the native aortic valve. However, these bioprostheses are challenging to implant in the subcoronary position. Methods: All consecutive patients who underwent a bioprosthetic aortic valve replacement (AVR) were included from our institutional database. Cox regression analysis was preformed to determine significant predictors for mid term mortality as well as all cause, cardiac, and heart failure readmission. Results: Patients in the subcoronary stentless group were older and more likely to be female and were likely to have a higher Society of Thoracic Surgery risk of mortality. Survival was superior in the stented AVR cohort at 30‐days (96.4% vs 90.5%; P < .001), 1‐year (90.5% vs 71.6%; P < .001), and 5‐year (74.5% vs 56.9%; P < .001) follow up. Acute kidney injury (16.22% vs 5.22%; P < .001) and blood product transfusion (70.27% vs 44.0%; P < .001) were higher in the stentless group. Multivariable analysis revealed subcoronary stentless implantation as a significant independent risk factor for mortality (hazards ratio: 1.92 [1.35, 2.72]; P < .001). Conclusion: Stentless porcine xenograft implantation with the Freestyle bioprosthetic in the subcoronary position can be successfully performed in select patients, but its use is associated with increased perioperative morbidity and mortality affecting midterm outcomes. Individual patient selection and surgeon experience are important to ensure favorable outcomes.